2022
DOI: 10.3389/fpsyg.2022.914125
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning multilingualism in source-based writing in L1, L2, and L3: The relation between source use and text quality

Abstract: In this article, we report on a study that investigates how master’s students consult external sources for reading-to-write integrated tasks in their L1 (Dutch), L2 (English), and L3 (French). Two hundred and eighty master’s students in professional communication wrote synthesis texts based on three external sources, including a report, a web text, and a newspaper article in their L1 (Dutch), and in L2 (English), or L3 (French) at two moments of measurement, which were separated by an interval of 6 months. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 107 publications
0
1
0
Order By: Relevance
“…In addition to the areas of language addressed by the questionnaire, the learners' spontaneous reference to the sociocultural dimension of communication underscores the importance of sociocultural awareness in developing effective language skills. This result encourages further exploration of higher-level language competencies, such as strategic dimensions and pragmatics, in line with suggestions by Chau et al (2022). North et al, 2022;Piccardo et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition to the areas of language addressed by the questionnaire, the learners' spontaneous reference to the sociocultural dimension of communication underscores the importance of sociocultural awareness in developing effective language skills. This result encourages further exploration of higher-level language competencies, such as strategic dimensions and pragmatics, in line with suggestions by Chau et al (2022). North et al, 2022;Piccardo et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…This finding underscores the need to consider the influence of one's native language, not only in terms of potential transfer but also in understanding the dynamics of language interactions in a multilingual context. Chau et al (2022) emphasized the need for further investigation into cross-linguistic transfer in the context of third language acquisition, highlighting that the existing body of L3 research has primarily concentrated on low-level language components, such as vocabulary and syntax, as evidenced by the studies discussed above. Their study explored the text quality of master's students in professional communication as they engaged in reading-to-write integrated tasks in their L1 (Dutch), L2 (English), and L3…”
Section: Perceived Positive Language Interaction (Ppli)mentioning
confidence: 99%
“…The logging data are time-coded and can be analyzed in different ways providing insights into several aspects of the writing process (Leijten & Van Waes, 2013). Previous studies on synthesis writing using keystroke logging have provided information on the use of sources during the writing process (Chau et al, 2022;Leijten et al, 2017;Vandermeulen, van den Broek, et al, 2020c;. The study by Valenzuela and Castillo (2022) in this special issue adds to existing keystroke logging studies on source-based writing by not only looking into reading times and switches between production and reading, but also by focusing on pausing behavior during production.…”
Section: Toolsmentioning
confidence: 99%
“…In a context where multilingualism is in the spotlight (May 2013), it is curious to note that even academic writing in FL English has not been studied notably in environments where English is not the surrounding language (Langum and Sullivan 2020), not to speak of writing in other languages. Studies on the activation of other languages in L3+ use have almost exclusively designed tasks where the use of external help is not allowed; Chau et al (2022) also point to the lack of processoriented research on source use in writing, which complicates explaining and contrasting findings. In studies of crosslinguistic interaction, picture telling and argumentative tasks based on personal opinion and knowledge have been popular (Cenoz andGorter 2011, Orcasitas-Vicandi 2021).…”
Section: Previous Studies On Multilingual Writing Processes and Exter...mentioning
confidence: 99%
“…Some of the following example studies have been selected because of they focus on multilinguals, and specifically source use during writing. Others are not necessarily multilingual, but have proportioned means to visualise the process and, therefore, serve as examples of approaches taken so far: Chau et al 2022 had a research design quite similar to the one reported in this article. They used Inputlog for a synthesis writing task whose aim was to compare students' behavior writing texts in three languages (L1 Dutch, L2 English, L3 French, each text in a different target language).…”
Section: Previous Studies On Multilingual Writing Processes and Exter...mentioning
confidence: 99%